Biaya Produksi, Biaya Operasional, Volume Penjualan dan Laba Bersih Perusahaan Makanan dan Minuman Terdaftar di BEI - Ali, Hilyana Rahma Chairunnisa; Mahsina, Mahsina; Fauziah, Dien Ajeng (Equity: Jurnal Akuntansi, 2024)
This study aims to determine the effect of production costs, operating costs and sales volume on net income in food and beverage companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The method used in this research is descriptive quantitative method. The population in this study were food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period totaling 90 companies. The method of determining the research sample using purposive sampling, after sorting based on the criteria the number of research samples was 32 companies and the number of observations was 128 company data. Based on the results of the study, it shows that partially production costs have a significant positive effect on net profit, production costs have a negative but not significant value on net profit, and sales volume has a significant negative effect on net profit.